PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS SMART APPS CREATOR (SAC) MATERI PERUBAHAN BENTUK ENERGI PADA SISWA KELAS IV SDN 04 PULAU PUNJUNG - Dea Allysa Putri; Martiya Nurni Khairita, Dhara Atika Putr (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Research on the development of interactive learning media based Smart Apps Creator (SAC) material on changes in the form of energy in grade IV students of SDN 04 Pulau Punjung aims to evaluate the validity, practicality, and effectiveness of Smart Apps Creator (SAC) media in the development of interactive learning media. The validity, practicality, and effectiveness of Smart Apps Creator (SAC) media in the learning material on changes in the form of energy for grade IV students. Subjects the research subjects consisted of 16 students at SDN 04 Pulau Punjung. The method used is research and development (R&D) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Data collected data collected includes quantitative and qualitative data through validation tests of materials, media, and language, as well as a practicality questionnaire filled out by teachers and students. The trial was conducted on small and large groups. Validation results validation results showed that the average material validation reached 84%, 91% media validation, and 89% language validation, all of which are included in the “Very Valid” category. The practicability of SAC media based on teacher and student responses reached 100%, indicating the “Very Practical” category. In addition, the effectiveness of this interactive learning media obtained a value of 87.5%, which is also classified as “Very Effective”. Effective”. With the existence of interactive learning media based on Smart Apps Creator (SAC) can help students in learning.